Lived experiences of high ability underachieving Filipino college students in STEM a phenomenological study - Oyzon, Maria Vanessa P. Lusung; Koo, Grace S.; Muega, Maricris B. Acido; Ho, Leticia Penano; Joaquin, Ma. Nympha B.; Yangco, Rosanelia T. (Quezon City College of Education, University of the Philippines Diliman, 2018)
Qualitative research was utilized to conduct this study on high ability Filipino college students enrolled in STEM programs in a state university and their underachievement experiences. The research questions that guided the study were: (1) What are the lived experiences of high ability Filipino college students who underachievement? What factors, contexts or situations influenced the students'experiences of high ability underachievement? (2) What is the essence of the underachievement experiences of high ability Filipino college in STEM?
Dissertation
Includes bibliographical references (pages 255-267).
Keywords: Underachievers -- Education -- Philippines; College students -- Conduct of life. -- Philippines; College students -- Rating of -- Philippines; Qualitative research